2014
DOI: 10.1016/j.envpol.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the caesium-137 flux adsorbed to suspended sediment in a reservoir in the contaminated Fukushima region in Japan

Abstract: We estimated the flux of caesium-137 adsorbed to suspended sediment in the Kusaki Dam reservoir in the Fukushima region of eastern Japan, which was contaminated by the Fukushima Nuclear Power Plant accident. The amount and rate of reservoir sedimentation and the caesium-137 concentration were validated based on the mixed-particle distribution and a sediment transport equation. The caesium-137 and sediment flux data suggested that wash load, suspended load sediment, and caesium-137 were deposited and the discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Overall, the literature clearly demonstrates that the majority of soil erosion and concomitant radiocesium migration, coincides with extreme rainfall-runoff events (Minoura et al, 2014;Mouri et al, 2014;Nagao et al, 2013;Onishi et al, 2014). In fact, most sediment and radiocesium migration is thought to occur during short flood events that may occur 1e2 times per year .…”
Section: Radiocesium Mobilization: Rainfall Regimementioning
confidence: 96%
See 2 more Smart Citations
“…Overall, the literature clearly demonstrates that the majority of soil erosion and concomitant radiocesium migration, coincides with extreme rainfall-runoff events (Minoura et al, 2014;Mouri et al, 2014;Nagao et al, 2013;Onishi et al, 2014). In fact, most sediment and radiocesium migration is thought to occur during short flood events that may occur 1e2 times per year .…”
Section: Radiocesium Mobilization: Rainfall Regimementioning
confidence: 96%
“…Mouri et al (2014), Yamada et al (2015) and Kurikami et al (2013) demonstrated that reservoir management could assist in the control of radiocesium fluxes. The challenge with the management of these reservoirs in the temperate/monsoonal climate in the Fukushima region is that occasional water releases are required for their safe operation.…”
Section: Radiocesium Storage: Reservoirs and Damsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, large amount of radionuclides have been released into water, soil, and air after the Fukushima Daiichi Nuclear Power Plant Disaster. As a result, the treatment of radioactive wastewater has drawn growing attentions all over the world [2,3]. Among the radionuclides found in water, 137 Cs and 90 Sr are the most hazardous and abundant contaminants due to their long half-lives and high radioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the majority of soil erosion and concomitant radiocesium migration was reported to coincide with extreme rainfall events (Mouri et al, 2014;Nagao et al, 2013;Onishi et al, 2014). For example, reported that most sediment-bound radiocesium migration occurs in flood events that may only occur 1 to 2 times per year.…”
Section: Introductionmentioning
confidence: 99%